5x+3=6x-14

Simple and best practice solution for 5x+3=6x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3=6x-14 equation:


Simplifying
5x + 3 = 6x + -14

Reorder the terms:
3 + 5x = 6x + -14

Reorder the terms:
3 + 5x = -14 + 6x

Solving
3 + 5x = -14 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3 + 5x + -6x = -14 + 6x + -6x

Combine like terms: 5x + -6x = -1x
3 + -1x = -14 + 6x + -6x

Combine like terms: 6x + -6x = 0
3 + -1x = -14 + 0
3 + -1x = -14

Add '-3' to each side of the equation.
3 + -3 + -1x = -14 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = -14 + -3
-1x = -14 + -3

Combine like terms: -14 + -3 = -17
-1x = -17

Divide each side by '-1'.
x = 17

Simplifying
x = 17

See similar equations:

| 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x | | 5/10+7/3 | | (2x-3)(x^3-x^2+3x+5)=0 | | 2x-2x+3=8 | | 72/x=8 | | 7=6q/4+8/4 | | 7*x=49 | | R-1/2(4R+2)=0 | | 80/x=8 | | x^3+14x^2-9x-324=0 | | 2x+x+4+x+x+x-x-3=92 | | 2(r+1)=9 | | -6.3(x+3.7)+7.65x=-1.1x-38.99 | | 2x/5=-8 | | 7x-14y=7 | | 7x+-14y=7 | | f-8-3f=37f+4 | | 3y-3=5y-5 | | f-8-3f=3-7f | | 84-3=6y+17 | | 11x=7x-20 | | 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) | | 2(2k-5)-k=4-(3k+7) | | 49-x=14 | | -16-8= | | 26X+12=5(5X+7) | | 10+2-x/3=7 |

Equations solver categories